Legitimisation and Coercion in Political Discourse: Ghana Electoral Commission's Press Conference Media Report. - Jujugenia, Wilson Awiah; Afful, Joseph Benjamin Archibald; Kyei, Emmanuel (Journal of Applied Linguistics, 2025)
Emerging democracies and post-conflict nations are now stabilizing and democratizing as a result of elections. This study delves into power dynamics within media discourse, focusing on the press conference held by the Ghana Electoral Commission concerning the acquisition of a new biometric voter management system. Drawing from Chilton's (2004) framework of coercion, legitimisation, and delegitimisation, it investigates how the conference escalated political tensions by reiterating the Commission’s decision, rebutting opposition claims, and emphasizing the legitimacy of the new system. Using qualitative content analysis, the study offers a nuanced examination of language usage, highlighting inclusion and distancing techniques, along with ideological underpinnings, employed by the Commission to justify the procurement. Notably, descriptive terms like "expired," "bloated," and "out-of-life" are utilized to characterise the current voter register, aiming to underscore the necessity of the proposed changes. Keywords : press conference; party; election; institutional discourse; coercion.